Features of the Unpublished Katigbawan Festival Dance of Catigbian, Bohol - Cagulada, Elian Rose; Bulilawa, Rafunzel Y. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The Katigbawan Festival in Catigbian, Bohol, is a celebration deeply rooted in the town's cultural heritage. Among its vibrant components is a dance that encapsulates the spirit and identity of the community. Over the years, cultural practices have undergone transformations, and without careful documentation, the essence of these dances may be lost. In an age of globalization, sustaining local cultural practices is critical to retaining a distinct identity. This study aimed to identify and analyze the distinguishing characteristics of Katigbawan Festival Dance; the symbolism it conveys in the costumes and dance equipment/props used; the purpose of creating the dance; the values demonstrated in the Katigbawan Dance Steps; and the preservation initiatives implemented by the LGU. This study utilized qualitative descriptive research method with interview guide questions serving as data-gathering methods. The analysis finds that the Katigbawan Festival's basic dance steps are classified as festival dance, with motions arranged within time signatures of 2/2, 3/4, and 4/4. The research also sheds light on the symbiotic link that exists between the dance steps (Katigbi, Tigbaw, and Kabaw) and the matching costumes and props. These elements contain basic qualities such as thankfulness, ingenuity, power, and hard work. The costume represents the Carabao, also capturing the sense of nature which is the cave and the growth of the plant Katigbi. Dance equipment and props are artfully intertwined throughout the performance to represent the richness of natural resources.